(untitled) (The Agriculturists, 2020)
An experiment was carried out at the research field of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur during January 2017 to May 2017 to evaluate the effects of poultry litter based composts on morpho-physiological, yield and yield contributing characters of BRRI dhan28, a mega rice variety of Boro season in Bangladesh, under different water stress conditions. The plants were grown in pots, and the experiment was laid out in a factorial complete randomized design (CRD) with three replications. Factor A included three levels of fertilizer and compost amendments i.e. control (recommended inorganic fertilizer), compost (10 t ha-1) + inorganic fertilizer, compost (20 t ha-1) + without inorganic fertilizers, and factor B comprised of three water levels (continuous flooding, 100% field capacity and 75% field capacity). Different parameters such as plant height, tiller number, leaf number, leaf area, chlorophyll content, proline content and yield contributing characters were measured during the experiment. Most of the measured parameters were significantly influenced by irrigation levels with different fertilizer and compost amendments. The highest plant height and leaf number per hill were found in the treatment of compost (10 t ha-1) + inorganic fertilizer with 100% field capacity, though the maximum tiller number were produced by the interaction of control with flooding irrigation. The total chlorophyll was observed more in flag leaf by the interaction of control with 100% field capacity. The Proline content was observed more in flag leaf by the interaction of control with 75% field capacity. Relative water content was found more with the interaction of compost (10 t ha-1) + inorganic fertilizer with 75% field capacity. The highest effective tiller number hill-1 was found from control (19.33) at harvest. It was also observed that irrigation with 75% field capacity produced the lowest effective tiller (15.89) hill-1 at harvest. The longest panicle length (23.12 cm) was observed with the combined effect of compost (10 t ha-1) +inorganic with 75% field capacity. Thousand grain weight was found highest (18.83 g) in the interaction of compost (20 t ha-1 + without inorganic) with 75% field capacity. The interaction of compost (20 t ha-1 + without inorganic) and flooding irrigation gave the highest grain yield (33.17 g pot-1), which was statistically similar to the treatment of compost (10 t ha-1 + inorganic) with flooding irrigation. The highest harvest index was found from compost (20 t ha-1 + without inorganic) with flooding irrigation. The Agriculturists 2020; 18(1) 42-55